Profile of Sarcopenia in Elderly Patients at The Medical Rehabilitation Outpatient Department Dr. Soetomo General Academic Hospital - Farhan Nurdiansyah; Rwahita Satyawati Dharmanta; Hadiq Firdausi; Nuniek Nugraheni Sulistiawati (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
The elderly group is the age group that is most susceptible to geriatric syndromes, one of which is sarcopenia. Sarcopenia is a syndrome characterized by a progressive and overall decrease in muscle mass and skeletal muscle strength with an increased risk of disability, decreased quality of life, and death. Currently, research on sarcopenia profiles, particularly in Indonesia, is still limited. This research data is expected to help determine policies to improve the quality of services in the health sector. This study used the SARC-F questionnaire and the risk factor questionnaire for sarcopenia in elderly patients at the Medical Rehabilitation Outpatient Department RSUD Dr. Soetomo and has been permitted by the Penelitian dan Pengembangan (LitBang) section RSUD Dr. Soetomo, Surabaya. Several variables used in this study were gender, age, weight, height, body mass index (BMI), other diseases, physical activity, mood, and sarcopenia. There were 25 elderly patients at the Medical Rehabilitation Outpatient Department at RSUD Dr. Soetomo, Surabaya in November 2022”January 2023 which met the research inclusion criteria. The age of elderly patients at the Medical Rehabilitation Outpatient Department at RSUD Dr. Soetomo ranged from 60”81 years old, with an average of 60.48 years old. Female is the most common gender among the elderly patients at the Medical Rehabilitation Outpatient Department RSUD Dr. Soetomo, there are 17 (68%) female elderly patients. 80% of the elderly patients were in the young elderly group (60”69 years old), 16% in the middle elderly group (70”79 years old), and 4% in the old elderly group (â‰¥80 years old). Age, gender, other diseases, and physical activity are risk factors that have a significant correlation with sarcopenia among elderly patients at the Medical Rehabilitation Outpatient Department RSUD Dr. Soetomo.